Total cross section measurements with π- , Σ- and protons on nuclei and nucleons around 600 GeV/c - Dersch, U. (2000)
Total cross sections for Σ- and π- on beryllium, carbon, polyethylene and copper as well as total cross sections for protons on beryllium and carbon have been measured in a broad momentum range around 600GeV/c . These measurements were performed with a transmission technique in the SELEX hyperon-beam experiment at Fermilab. We report on results obtained for hadron-nucleus cross sections and on results for σtot(Σ-N) and σtot(π-N) , which were deduced from nuclear cross sections. © 2000 Elsevier Science B.V.